Bariatric surgery and the risk of alcohol‐related cirrhosis and alcohol misuse. (20th February 2021) - Mellinger, Jessica L.; Shedden, Kerby; Winder, G. Scott; Fernandez, Anne C.; Lee, Brian P.; Waljee, Jennifer; Fontana, Robert; Volk, Michael L.; Blow, Frederic C.; Lok, Anna S. F.
Abstract: Background & Aims: Bariatric surgery is common, but alcohol misuse has been reported following these procedures. We aimed to determine if bariatric surgery is associated with increased risk of alcohol‐related cirrhosis (AC) and alcohol misuse. Methods: Retrospective observational analysis of obese adults with employer‐sponsored insurance administrative claims from 2008 to 2016. Subjects with diagnosis codes for bariatric surgery were included. Primary outcome was risk of AC. Secondary outcome was risk of alcohol misuse. Bariatric surgery was divided into before 2008 and after 2008 to account for patients who had a procedure during the study period. Cox proportional hazard regression models using age as the time variable were used with interaction analyses for bariatric surgery and gender. Results: A total of 194 130 had surgery from 2008 to 2016 while 209 090 patients had bariatric surgery prior to 2008. Age was 44.1 years, 61% women and enrolment was 3.7 years. A total of 4774 (0.07%) had AC. Overall risk of AC was lower for those who received sleeve gastrectomy and laparoscopic banding during the study period (HR 0.4, P <.001; HR 0.43, P =.02) and alcohol misuse increased for Roux‐en‐Y and sleeve gastrectomy recipients (HR 1.86 and 1.35, P <.001, respectively). In those who had surgery before 2008, women had increased risk of AC and alcohol misuse compared to women without bariatric surgery (HR 2.1 [95% CI: 1.79‐2.41] for AC; HR 1.98 [95% CI 1.93‐2.04]). Conclusions: Bariatric surgery is associated with a short‐term decreased risk of AC but potential long‐term increased risk of AC in women. Post‐operative alcohol surveillance is necessary to reduce this risk.